Creeping flashover test methods, characteristics, and mechanisms of oil-paper insulation structures of power transformers - Bao, Yanyan; Wang, Feng; Liu, Kang; Tao, Bo (Frontiers in Materials, 2024)
Power transformers are critical equipment responsible for the transmission and transformation of electrical energy, and they are an important component of power system. Under the combined effects of electric field, thermal field, and mechanical stress, insulation degradation is prone to occur in oilpaper insulation structures. Among them, the "liquid-solid" interface formed by oil and oil-immersed pressboard is the weak point in transformer insulation, and extensive operational experience has shown that creeping flashover of insulating pressboard is a common fault in power transformers. Creeping flashover of insulating pressboard can rapidly destroy the insulation structure, leading to irreversible damage to the transformer and posing a serious risk of transformer accidents. In recent years, many scholars have conducted in-depth research on the characteristics and mechanisms of creeping flashover in oil-paper insulation structures using various experimental methods. They have obtained significant findings that have important theoretical and practical implications for optimizing the structure of power transformers and improving their reliability. This paper first introduces the characteristics of the electromagnetic environment inside the power transformer and the common forms of creeping flashover accidents in engineering. Then, classified according to the uneven degree of electric field and creepage distance of test electrodes used in relevant research, and the test methods and flashover characteristics of small size (<5 cm) and large size insulating pressboard under extremely uneven and slightly uneven electric fields are introduced respectively. Secondly, the existing breakdown model and mechanism theory of oil-paper insulation structure creeping flashover are summarized. Finally, the limitations of the existing creeping flashover test method of insulating pressboard are analysed, and the key issues to be solved are condensed. This review aims to provide readers with a comprehensive overview of the test methods, characteristics, and mechanisms of insulating pressboard creeping flashover.